KNOWLEDGE OF INFORMATION AND COMMUNICATION TECHNOLOGIES USAGE AMONG ARABLE FARMERS IN EKITI STATE, NIGERIA - AJAYI, G. T.; SOYEBO, K. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
The study focused on the knowledge of information and communication technologies (ICTs) usage among arable farmers in Ekiti State, Nigeria. A multi-stage sampling procedure was employed to select 240 respondents in the study area. Primary data was collected from the respondents through a well-structured interview schedule and analyzed using descriptive statistics as well as regression analysis. The mean age of the respondents was 54±14 years respectively, and had a mean household size of 6±3 persons. Most (87.5%) had formal education. More than half (55.8%) had no contact with extension agents. Mobile telephone (35.6%), radio (32.3%), and television (11.3%) were the most available ICTs. Awareness of ICTs by the respondents was 2.75. Awareness of mobile phones for making calls or text messages to co-farmers or family members (3.7), mobile phones used as electronic diary (3.2), radio for listening to agricultural programs (3.2), mobile phone to receive and disseminate information to transporters and laborers (3.0), television for getting information on farm inputs (2.9), mobile phone for farm business (2.8), mobile phone for market update (2.8) and FM radio for news and current affairs (2.8) and mostly (58.3%) had moderate knowledge of ICTs usage. Significant relationships exist between household size, extension agent contact, awareness level, and knowledge of ICT usage. Efforts should be made to increase farmers’ knowledge of ICTs usage especially computer-based technologies for documenting farm activities through extension agent contact, creating more awareness of ICTs, and providing incentives to acquire such ICTs tools for agricultural proficiency to enhance productivity.